A multidisciplinary investigation of the technical and environmental performances of TAML/peroxide elimination of Bisphenol A compounds from water12. Issue 18 (8th August 2017) - Onundi, Yusuf; Drake, Bethany A.; Malecky, Ryan T.; DeNardo, Matthew A.; Mills, Matthew R.; Kundu, Soumen; Ryabov, Alexander D.; Beach, Evan S.; Horwitz, Colin P.; Simonich, Michael T.; Truong, Lisa; Tanguay, Robert L.; et al.
Abstract : A multidisciplinary investigation of the technical and environmental performances of TAML/peroxide elimination of Bisphenol A compounds from water: destruction, oligomerisation, mechanisms, end product toxicity, and applications. Abstract : Designing technologies that mitigate the low-dose adverse effects of exposures to large-volume, everyday-everywhere chemicals such as bisphenol A (BPA, 1a ) requires an understanding of the scope of the exposures and the nature of the adverse effects. Therefore, we review the literature of, (i) the occurrences of1a in humans, waters and products and the effectiveness of widely deployed mitigation methods in1a stewardship and, (ii) the adverse effects of1a exposures on human cells and fish. Within this broad context, we present and evaluate experimental results on TAML/H2 O2 purification of1a contaminated waters. TAML/H2 O2 catalysis readily oxidizes BPA (1a ) and the ring-tetramethyl (1b ), tetrachloro (1c ), and tetrabromo (1d )-substituted derivatives. At pH 8.5, TAML/H2 O2 induces controllable, oxidative oligomerisation of1a (2-, 3-, 4-, and 5-unit species were identified) with precipitation, establishing a green synthetic pathway to these substances for biological safety characterisation and an easy method for near quantitative removal of1a from water. TAML/H2 O2 (24 nM/4 mM) treatment of1a (10 000 μg L −1 ) in pH 8.5 (0.01 M, carbonate) lab water effects a >99% reduction (to <100 μg L −1 1a ) within 30 min. Yeast oestrogen screens (YES) of the pH 8.5, TAML/H2 O2 treated, catalase quenched, and filtered oxidation solutions show elimination of1a oestrogenicity. Zebrafish developmental assays of TAML/H2 O2 treated, unfiltered, agitated pH 7, 1a solutions showed no significant incidences of abnormality among any of 22 endpoints—treated samples showed an insignificant increase in mortality. At pH 11, the TAML/H2 O2 oxidations of1a–d are fast with second order rate constants for the substrate oxidation process ( k II values) of (0.57–8) × 10 4 M −1 s −1 . The1a oxidation gives CO and CO2 (∼78%), acetone (∼25%) and formate (∼1%). In striking contrast with pH 8.5 treatment, no oligomers were detected. TAML/H2 O2 (150 nM/7.5 mM) treatment of1a (34 244 μg L −1 ) in pH 11 (0.01 M, phosphate) lab water effected a >99.9% reduction (to <23 μg L −1 1a ) within 15 min. The pH dependent behaviour of1a was examined as a possible origin of the differing outcomes. The 1 st and 2 nd p K a values of1a were estimated by fitting the pH dependence of the UV-vis spectra (p K a1 = 9.4 ± 0.3; p K a2 = 10.37 ± 0.07). At pH 8.5, coupling of the radical produced on initial oxidation evidently outcompetes further oxidation. A linear free energy relationship between the logarithm of the pH 11, k II values and the redox potentials of1a–d as determined by differential pulse voltammetry in CH3 CN is consistent with rate-limiting, electron transfer from the dianionic form of1a at pH 11, followed by a multistep, deep degradation without observation of 4-(prop-1-en-2-yl)phenol12, a common1a oxidation product—an improved synthesis of12 is described. Microtox® analyses of pH 12, TAML/H2 O2 treated1a solutions showed significantly reduced toxicity. The facility and high efficiency by which TAML/H2 O2 catalysis eliminates1a from water, by either mechanism, suggests a new and simple procedure for1a stewardship.